(untitled) (Revista de História da UEG (REVHIST), 2021)
The Teachers for Freedom (DPL) are an instrument in the struggle for new consensuses and for the construction of conditions for the hegemony of Jair Bolsonaro’s government. The foundation of this organization and the performance of its intellectuals are new elements in the sad scenario of the Brazilian political situation. The DPL is an instrument for mobilizing staff in support of the federal government and for the formation of a public opinion aligned with Bolsonaro’s proposals for public policies for education. The evidence studied in this research suggests that it is an organization created at the initiative of the military and civilians, linked to the current federal government. And, it was structured to act and collaborate in the development of conditions for an administrative and curricular reform within the scope of the Ministry of Education and educational institutions, based on a conservative, liberal and anti-democratic perspective. The article aims to understand the purposes of the organization, the performance and the ideology of the DPL. Articulating in the context of political science the analysis of primary sources with categorical foundations by A.Gramsci. The results achieved in this investigation point to elements of the characterization of the DPL’s political agenda and the social function it seeks to play in the current situation, to the detriment of scientific and democratic assumptions, in education and research institutions in Brazil. Keywords: Teachers for Freedom. Bolsonaro. Brazil. Contemporary politics. Gramsci.